Fouling dan Cleaning Membran Reverse Osmosis Tekanan Rendah untuk Aplikasi Daur Ulang Air Limbah Domestik - Retno Dwi Jayanti; I Nyoman Widiasa (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Separation process by reverse osmosis membrane for wastewater reuse is an advantage process because of feasible cost and able to produce high quality of product water. The used of RO membrane on wastewater reuse application is often limited by fouling phenomena, that is the accumulation of some types of foulant on the membrane surface. An understanding of the foulant types and the fouling mechanism is the key to success in RO membrane chemical cleaning. This review discusses numerous works about the fouling mechanisms and cleaning procedures.